ARAHAN PENGEMBANGAN OBYEK WISATA MENUJU PEMBANGUNAN PARIWISATA BERKELANJUTAN DI KABUPATEN WONOGIRI - Joko Wuri Nugroho, Komarsa Gandasasmita, dan Manuwoto (Universitas Gadjah Mada, 2015)
The development of the tourism sector in Wonogiri Regency is still more left behind than PacitanRegency and Gunungkidul Regency. This problem may possibility by the weakness in the policy fromWonogiri Regency Government. Thus, we need research which have purposes : (1) to know economicdevelopment in Wonogiri Regency (2) to know tourism objects which have potential amendable,(3) to know efficiency from tourism objects management, and (3) formulate direction and strategiesdevelopment of potential tourism object for sustainable development. Spot of the research in 40tourism objects with survey and interview respondent. Analysis data use entropi method, scoringmethod, description method, DEA method, AHP method, IFAS method, EFAS method, Matrix IEmethod, Matrix Space method and A’WOT method. The results show five county with best economicdevelopment are Wonogiri, Ngadirojo, Pracimantoro, Jatisrono and Baturetno; there five tourismobjects with potentially classification to develop are Setren Girimanik, Sendang Asri, Karamba Cakaran,Puppet Tourism Village Kepuhsari and Karst Museum; Tourism objects with efficient management areSetren Girimanik, Sendang Asri and Karst Museum; Tourism management from Gunungkidul Regencycan adapt in Wonogiri Regency; Priority strategies which recommended are make four tourism regionand increasing tourism objects accessibility.